Optimal Design of a Delayed Feedback - Semenič, N.; Sarjaš, A.; Chowdhury, A.; Svečko, R. (Elektronika ir Elektrotechnika, 2014)
In this paper robustness analysis and simultaneous stabilization of a semiconductor laser (SL) with a delayed optoelectronic feedback (OEF) is studied. Using the theory of stability radius maximal allowed norm bounded perturbations of the SL in contrast to stabilizable intervals of OEF parameters are obtained. Using proposed algorithms we can analyse the effect of interdependencies of uncertainties of the OEF and SL parameters and design an optimal OEF according to specific robustness constraints. DOI: http://dx.doi.org/10.5755/j01.eee.20.8.5917